The Human Perspective in Consumer Ethics and Animal Welfare Issues: Envisioning a Future for Change - Bonadonna, Alessandro; Bollani, Luigi; Peira, Giovanni (Journal of Advances in Management Sciences & Information Systems, 2022)
Animal welfare has been a subject of interest for the European Union since the 1970s, with the definition of animal protection guidelines during international transport, on farms and for slaughter. However, the Legislator’s concern found its highest expression in the Animal Welfare Protocol of the Treaty of Amsterdam, where animals are defined as sentient beings, therefore worthy of attention in the policies developed by the European Union and its Member States. Nowadays, the interpretation of the animal welfare concept as an element that contributes to increasing profitability is also integrated by respect for the animal’s feelings and, consequently, the related different biological manifestations. Food scandals and diseases, on the one hand, and the emergence of a new approach to consumer ethics, on the other, have also strongly sensitized the European population about the importance of protecting animal welfare. Based on the above considerations, this study provides a framework to understand whether animal welfare should merely be considered as a product of EU strategies dedicated to the economic and competitive performance of agricultural and agro-industrial enterprises or whether it can also be assessed as a useful tool to minimize the environmental impact, through breeding practices and food habits, and therefore encourage more sustainable development.